Carers' perspectives on the presentation of community-acquired pneumonia and empyema in children: a case series. Issue 5 (4th September 2012) - Crocker, Joanna C; Evans, Meirion R; Butler, Christopher C; Hood, Kerenza; Powell, Colin V E
Abstract : Objective: To describe carers' perceptions of the development and presentation of community-acquired pneumonia or empyema in their children. Design: Case series. Setting: Seven hospitals with paediatric inpatient units in South Wales, UK. Participants: Carers of 79 children aged 6 months to 16 years assessed in hospital between October 2008 and September 2009 with radiographic, community-acquired pneumonia or empyema. Methods: Carers were recruited in hospital and participated in a structured face-to-face or telephone interview about the history and presenting features of their children's illnesses. Responses to open questions were initially coded very finely and then grouped into common themes. Cases were classified into two age groups: 3 or more years and under 3 years. Results: The reported median duration of illness from onset until the index hospital presentation was 4 days (IQR 2–9 days). Pain in the torso was reported in 84% of cases aged 3 or more years and was the most common cause for carer concern in this age group. According to carer accounts, clinicians sometimes misjudged the origin of this pain. Almost all carers reported something unusual about the index illness that had particularly concerned them—mostly non-specific physical symptoms and behavioural changes. Conclusions: Pain in the torso and carer concerns about unusual symptoms in their child may provide valuable additional information in a clinician's assessment of the risk of pneumonia in primary care. Further research is needed to confirm the diagnostic value of these features.